Oil Price Shock and its Impact on the Macroeconomic Variables of Pakistan: A Structural Vector Autoregressive Approach - Malik, Kashif Zaheer; Ajmal, Haram; Zahid, Muhammad Umer (International Journal of Energy Economics and Policy, 2017)
This study examines the dynamic effects of the oil price shocks on the key macroeconomic variables of Pakistan. A Structural Vector Autoregressive model is used on yearly data from 1960 to 2014. The impulse response functions indicate that the oil price shocks depress the real gross domestic product while the real exchange rate also experiences depreciation. However, the long-term interest rate and the inflation rate rise as a result of a positive oil price shock. The unanticipated changes in these macroeconomic variables threaten the economic stability of Pakistan; specifically, higher inflation and interest rates hamper the economy’s growth rate. Lastly, the variance decomposition analysis illustrates that the oil price shocks have the most impact on the inflation rate of Pakistan. Keywords: SVAR; Oil Price Shocks; Macroeconomic Variable JEL Classifications: C22; E40; E31; E50; Q43